1995
DOI: 10.1002/jez.1402710207
|View full text |Cite
|
Sign up to set email alerts
|

Role of steroids in antler growth of red deer stags

Abstract: A series of six studies were carried out in red deer stags to test hypotheses concerning the importance of steroid control of velvet antler growth and to investigate mechanisms by which these hormones exert their effects. Medroxyprogesterone acetate (MPA) an LH inhibitor administered to stags during hard antler caused premature antler casting, reduced subsequent antler weight and caused a reduction in the LH and testosterone responses to GnRH. In two separate studies blockade of testosterone receptors with cyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 23 publications
6
60
0
Order By: Relevance
“…The increase in cortisol pulse height, pulse nadir and pulse amplitude in November indicates that there is a shift in the regulation of the HPA axis during spring. Changes in height and amplitude reflect to some extent the increased responsiveness of the adrenal gland to ACTH seen at this time of year (Suttie et al 1995, Cassidy 1996. However, the threefold increase in cortisol pulse parameter values compared with that seen during the rut would suggest that the adrenal gland changes are also accompanied by changes in endogenous ACTH secretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in cortisol pulse height, pulse nadir and pulse amplitude in November indicates that there is a shift in the regulation of the HPA axis during spring. Changes in height and amplitude reflect to some extent the increased responsiveness of the adrenal gland to ACTH seen at this time of year (Suttie et al 1995, Cassidy 1996. However, the threefold increase in cortisol pulse parameter values compared with that seen during the rut would suggest that the adrenal gland changes are also accompanied by changes in endogenous ACTH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for a seasonal rhythm in adrenal activity or responsiveness in deer varies between species and studies, with seasonal changes reported in white-tailed deer (Bubenik et al 1983), reindeer (Rangifer tarandus) (Nilssen et al 1985), axis deer (Axis axis) (Chapple et al 1991) and red deer (Suttie et al 1995, Cassidy 1996 but not in Eld's deer (Monfort et al 1993) or in another study on axis deer (Bubenik & Brown 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Castration of male deer carrying hard antlers as well as the administration of substances interfering with testosterone production or inhibiting both testosterone production and its action at the receptor level causes premature antler casting (Wislocki et al, 1947;Lincoln, 1971;Muir et al, 1982;Jaczewski, 1985;Bubenik GA et al, 1987, 2002Goss et al, 1992;Schams et al, 1992;Kierdorf U et al, 1993Suttie et al, 1995). Administration of testosterone or estradiol to males in hard antler postpones antler casting beyond the normal date (Goss, 1968).…”
mentioning
confidence: 99%
“…When male deer carrying velvet antlers are castrated (Blauel, 1935;Wislocki et al, 1947;Goss, 1968) or treated with the antiandrogen cyproterone acetate (Bubenik GA et al, 1975;Kolle et al, 1993), the velvet is not shed. So far, it is a matter of debate whether or not antler growth itself requires (direct or indirect) stimulation by low levels of androgens (Bubenik GA, 1983Schams et al, 1992;Kolle et al, 1993;Suttie et al, 1995;Bartoš et al, 2000;Sadighi et al, 2001).…”
mentioning
confidence: 99%